A review of Megalogomphus sumatranus (Krüger, 1899) and its allies in Sundaland with a description of a new species from Borneo (Odonata: Anisoptera: Gomphidae) - Dow, Rory A.; Price, Benjamin W. (Zootaxa, 2020)
Megalogomphus sumatranus (Krüger, 1899) and its allies in Sundaland are reviewed. The accessory genitalia of the males of this genus, hardly considered previously, are found to be taxonomically informative. The taxon from Borneo previously treated as M. sumatranus is described from both sexes as M. buddi sp. nov. (holotype ♂ Sungai Datai, Nanga Bloh, Lanjak Entimau Wildlife Sanctuary, Kapit Division, Sarawak, Malaysia, 22 viii 2013, leg. J. anak Awan & M. anak Adau; deposited at the Naturalis Biodiversity Center, Leiden, the Netherlands). Megalogomphus borneensis (Laidlaw, 1914), described as a subspecies of M. icterops (Martin, 1903) and subsequently relegated to the synonymy of that species, is considered to be a distinct species. Megalogomphus icterops is however considered to be a junior synonym of M. sumatranus. A re-description of the holotype of Megalogomphus borneensis is provided as is the first description of the female. Descriptive notes with illustrations of Megalogomphus sumatranus are given.